Senior learning in Taiwan: achievements and challenges - Findsen , Brian; Wei, Hui-Chuan (Adult Education Discourses, 2023)
This article traces some of the major achievements of a local Taiwanese initiative – the Active Ageing Learning movement, which provides seniors with greater opportunity to engage in learning in later life, whether for expressive or vocational reasons. Taiwan has faced considerable increases in the numbers of older people proportionately in the general population as it moves from an “aged society” to a “super-aged society”. This article’s purpose is to provide a historical account of developments and challenges in senior learning as an example of an East Asian nation’s efforts to move away from social welfare paternalism to older citizens as active educative agents in a mainly post-work environment. Data were derived from a combination of document analysis of policy documents and research located within professional practice. The pathway towards a more sustainable learning society in which seniors play an important role has been met with resistance and has faced several challenges. In addition to analysing achievements, this article investigates these challenges and provides suggestions for greater clarity and integration of learning opportunities for elders in Taiwan. The article concludes that both challenges and successes need acknowledgment. As a major recommendation, in order to meet the demands of a super-aged society, Taiwan can profit from planning and implementing regional centres as sites of learning located conceptually and physically between top-down government-driven directives and more democratic bottom-up community-based initiatives. To be successful, such centres will require substantive training and development and a collective push from the state, civil society members and private enterprise.